Agricultural Input Subsidies: The Recent Malawi Experience - Chirwa, Ephraim (Oxford University Press, 2013)
Agricultural input subsidies were a major feature of development policies in rural economies until the 1980s. Continuing rural poverty with low productivity and fertilizer use in smallholder staple crops has led to their resurgence in Africa. These subsidies are, however, controversial with claims of both large food security benefits and unsustainable, inefficient resource use. This book reviews current theory and evidence on the strengths and weaknesses of these programmes and the effects of programme context, design, and implementation. Theoretical arguments for agricultural subsidies are based on input promotion where farmers' private costs (benefits) are higher (lower) than wider economic costs (benefits). These arguments, and concerns about inefficiency and diversion, are reviewed and extended to consider input affordability constraints and 'smart' rationing and targeting. Recent programmes in Africa have a variety of generally producer-focused objectives, with varied implementation and programme outcomes. Most pay little attention to consumer interests and potential contributions to wider growth. A detailed examination of Malawi's controversial agricultural input subsidy programme follows. Drawing on a wide range of information sources, the political and agro-economic contexts of the programme are examined, with evidence on its implementation and impacts from 2005 to 2011. Positive impacts are recorded on beneficiaries' production, incomes, food consumption, school enrolment, child health, and reduced need for earnings from undertaking casual labour for others. There is evidence of indirect economy-wide impacts, but this is not as strong as might be expected. Targeting and graduation are identified as critically important issues requiring continuing attention.